2021
DOI: 10.33258/birci.v4i1.1726
|View full text |Cite
|
Sign up to set email alerts
|

Public Services Advertising Community Movement Program “GERMAS” Public Health, Batu Bara District through Radio Odan FM

Abstract: The purpose of this study was to find and study about public services advertising community movement program “GERMAS” public health.  This research is in the form of field research. Field research is research that is aimed directly at the location of the research to be studied, namely in a community, agency or company to search for data and then observe and conclude. Based on the results of the discussion in the previous chapter, it can be concluded that the public service advertisement broadcast of the GERMAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Singh, K. P. et al tested the variables using multivariate regression analysis with the aim of determining the role of public service advertising in raising health awareness [23]. Hasibuan, S. et al looked for and studied public service advertising community campaigns in the form of a field study [24]. Kim, E. A. et al found that empathetic narratives were superior to nonnarratives in public service advertising, i.e., the level of emotion that motivated bystanders was more favorable for advertising communication in public advertisements [25].…”
Section: Introductionmentioning
confidence: 99%
“…Singh, K. P. et al tested the variables using multivariate regression analysis with the aim of determining the role of public service advertising in raising health awareness [23]. Hasibuan, S. et al looked for and studied public service advertising community campaigns in the form of a field study [24]. Kim, E. A. et al found that empathetic narratives were superior to nonnarratives in public service advertising, i.e., the level of emotion that motivated bystanders was more favorable for advertising communication in public advertisements [25].…”
Section: Introductionmentioning
confidence: 99%